2022
DOI: 10.1039/d1ta09956f
|View full text |Cite
|
Sign up to set email alerts
|

Augmented photoelectrochemical water reduction: influence of copper vacancies and hole-transport layer on CuBi2O4 photocathode

Abstract: A ternary metal oxide CuBi2O4 has received immense attention in the research field of photoelectrochemical(PEC) for water or CO2 reduction owing to its ideal optical bandgap and positive photocurrent onset...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Based on the CB band potentials, the photogenerated holes easily transfer from the IO-CBO-3 photocathodes to externally connected Pt electrodes, where the holes are oxidized to form oxygen. The photogenerated electrons contribute to hydrogen production on the surface of the IO-CBO-3 nanostructures. The interconnected porous structures contribute toward a reduced recombination rate and promote the charge-carrier’s transportation rate, resulting in high stability and an enhanced hydrogen evolution rate.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the CB band potentials, the photogenerated holes easily transfer from the IO-CBO-3 photocathodes to externally connected Pt electrodes, where the holes are oxidized to form oxygen. The photogenerated electrons contribute to hydrogen production on the surface of the IO-CBO-3 nanostructures. The interconnected porous structures contribute toward a reduced recombination rate and promote the charge-carrier’s transportation rate, resulting in high stability and an enhanced hydrogen evolution rate.…”
Section: Resultsmentioning
confidence: 99%
“…Gopannagari et al attached Fe-doped NiO x thin layer onto the copper vacancyinduced CuBi 2 O 4 (CBOÀ O 2 ) back-interface for photoelectrochemical water reduction. [53] The CBOÀ O 2 photocathode exhibited a higher hole-concentration and the Fe : NiO x layer acted as an efficient hole-transport layer at the back interface (Figure 8e). Fe : NiO x À HTL effectively extracted the photogenerated holes from the CBOÀ O 2 photocathode with high a hole concentration.…”
Section: Hole Transport/storage/blocking Layermentioning
confidence: 99%
“…Many studies on metal oxides consider their vacancy properties due to the interaction between gaseous oxygen and oxide lattice. [ 164 ] It has been shown that metal oxide photocathode with Cu vacancies can enhance the kinetics of interface reactions between electrode and electrolyte. However, the role of vacancies in preventing charge recombination has not been addressed.…”
Section: Applications Of Defective Photocathode In Energy Conversionmentioning
confidence: 99%
“…[180] In addition, the possible products of nitrogen reduction are NO 2 , N 2 , NH 3 , and H 2 , and increasing the FE of NO 3 to NH 3 remains a challenge. [181] [164] Copyright 2022, Royal Society of Chemistry. g) Kinetic model showing two competitive pathways for the decay of the excited charge-transfer state.…”
Section: N 2 Fixationmentioning
confidence: 99%
See 1 more Smart Citation